“Identity issues” and lines of internal divisions in Montenegro - Đukanović Dragan (Međunarodni Problemi)
The history of Montenegro in the 20th and the early 21st century shows that the divisions were very prominent, these including the moment when the Kingdom of Montenegro had been created (after 1918), the period during World War II (1941-1945) as well as the time when its state and legal position was to be resolved. Similar lines of divisions in the Montenegrin society became dominant again during the dissolution of former SFR Yugoslavia (1991-1999) as well as immediately before and after the referendum on the status of the state in 2006 concerning primarily the set of the so-called identity issues. Those issues include the images and contents of Montenegro’s state symbols, the official language (the Montenegrin language since 2007) and the status of the canonically unrecognised Montenegrin Orthodox Church. At the same time, the author points to the disagreements of political actors in Montenegro regarding its membership in the NATO. This prevents the possibility of achieving as broad as possible consensus on the foreign policy identity and orientation of this country. Finally, the author concludes that it is necessary to achieve a broad internal consensus and make a compromise in Montenegro concerning the set of identity issues mentioned above in order to prevent the traditional division in the society. [Projekat Ministarstva nauke Republike Srbije, br. OI 179023: Srbija u savremenim međunarodnim integrativnim procesima - spoljnopolitički, međunarodni, ekonomski, pravni i bezbednosni aspekti]